2009
DOI: 10.1097/psy.0b013e3181baef05
|View full text |Cite
|
Sign up to set email alerts
|

A General Enhancement of Autonomic and Cortisol Responses During Social Evaluative Threat

Abstract: Objective The idea that distinct psychosocial factors may underlie specific patterns of neuroendocrine stress responses has been a topic of recurrent debate. We examined a recent contribution to this debate, the Social Self Preservation Theory, which predicts that stressors involving social evaluative threat (SET) characteristically activate the hypothalamic-pituitary-adrenal (HPA) axis. Methods Sixty-one healthy university students (31 females) performed a challenging speech task in one of three conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
108
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(119 citation statements)
references
References 61 publications
6
108
3
2
Order By: Relevance
“…Others have proposed that sympathetic and HPA activation can be dissociated in some circumstances (Frankenhaeuser, 1982;Dickerson and Kemeny, 2004). However, there is also substantial evidence that they frequently covary, such that variations in the magnitude of the acute stress reactions of the sympathetic nervous system, as indexed by cardiac reactivity, predict subsequent variation in HPA reactions, as indexed by cortisol reactivity (Cacioppo, 1994;Al'Absi et al, 1997;Bosch et al, 2009). The present results suggest that disordered eating behaviour may be characterised by dysregulation in both branches of the stress response system.…”
Section: Discussionmentioning
confidence: 99%
“…Others have proposed that sympathetic and HPA activation can be dissociated in some circumstances (Frankenhaeuser, 1982;Dickerson and Kemeny, 2004). However, there is also substantial evidence that they frequently covary, such that variations in the magnitude of the acute stress reactions of the sympathetic nervous system, as indexed by cardiac reactivity, predict subsequent variation in HPA reactions, as indexed by cortisol reactivity (Cacioppo, 1994;Al'Absi et al, 1997;Bosch et al, 2009). The present results suggest that disordered eating behaviour may be characterised by dysregulation in both branches of the stress response system.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the absence of a social evaluative threat as indicated in previous studies (al 'Absi et al, 1997;Bosch et al, 2009;Dickerson & Kemeny, 2004;Gruenewald et al, 2004;Rohleder et al, 2006). The results suggest that a speech without social evaluative threat is not stressful enough to elicit a physiological reaction.…”
Section: Discussionmentioning
confidence: 48%
“…Thus, it is highly possible that cortisol levels before the speech were similar to or lower than after the speech. The frequently reported, significant increase in salivary cortisol 10 to 20 minutes after a speech (Bosch et al, 2009;Het et al, 2009;Kirschbaum et al, 1993;Rohleder et al, 2006) is another important consideration, which might have caused the cortisol response to the speech observed in this study to be underestimated. It is suggested that in future studies, the cortisol level should be assessed just before and 10 to 20 minutes after the speech in order to obtain the most valid results.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations